The Role of Afghanistan in the Uighur Separatist Movement: Why the People’s Republic of China should take over NATO after 2014 - Ainuvee, Kristina (Politikon: The IAPSS Journal of Political Science, 2015)
As with the U.S. withdrawal from Afghanistan in the end of 2014, there is no obvious replacement for the place of peace guarantor in the country and in the region. The most apparent successor is the People’s Republic of China for a number of reasons. First, Afghan extremists are considered to be connected with the rebels from China’s province Xinjiang. Not only they undermine internal stability in China, but they also engage in illegal drug trade and are a very important point in heroine trade route across Central Asia up to Central Europe. Although the Chinese law enforcers are addressing this issue, there is no clear success in the near future. That being said, in order to deter the flourishing illegal drug trade, the revenues from which are used to finance the uprisings, China needs to step up as a replacement of the U.S.-led forces in Afghanistan after 2014.